DEVELOPMENT OF PROSPECTIVE EFL TEACHERS’ QUESTIONING SKILLS IN CLASSROOM DISCOURSE: INTERDISCIPLINARY APPROACH - Tetiana Yeremenko; Iryna Lukyanchenko; Angelina Demchuk (Novìtnâ Osvìta, 2022)
The research is devoted to the problem of mastering pre-service EFL teachers’ specific proficiency in using questions as an effective tool in the EL classroom discourse and university discourse. The purpose of the paper is to submit the teaching scheme of training pre-service EFL teachers’ questioning skills, encouraging them to work out their own teaching strategies in the future professional activity. The authors substantiate the possibility of improving MA students and pre-service EFL teachers’, questioning skills via suggested teaching scheme actualising interdisciplinary connections between the practical course (“English Communication in Academic Discourse”) and theoretical-practical course (“Theory and Practice of Speech Communication”) and students’ teaching practice that are majors of the Master’s degree curriculum. The emphasis is laid on the content level – EL classroom discourse acquisition. The experiment was conducted involving 90 MA students, pre-service EFL teachers, of South-Ukrainian National Pedagogical University named after K. D. Ushynsky to clarify the efficiency of the suggested teaching scheme. Data were obtained and analysed via pre-experimental assessment stage, experimental teaching (implementation of the suggested teaching scheme), post-experimental assessment stage employing quantitative and qualitative research methods. Data collection procedures included pedagogical observation, analysis of the students’ results, self-assessment questionnaire, student’s opinion questionnaire, statistical and mathematical processing of obtained data. The findings of the research indicate that the suggested teaching scheme using interdisciplinary approach helps students become more proactive in constructing their knowledge of questions linguodidactic potential, to transform the acquired knowledge to new ways of verbal behaviour, to model successful communication in the EL classroom through appropriate questions, and to modify their teaching styles. The authors come to the conclusion that it is mandatory to include special consecutive training covering initially purely practical courses with a gradual shift to theoretical-practical ones, and finally – teaching practices as a closing step to improve students’ proficiency in using questions effectively in the EL classroom school and university discourse.